Assessment of Water Supply Infrastructure and Service Challenges in Depok City - Chandra Rahmansyah; Firdaus Ali (Riviera Publishing, 2025)
This study assesses the infrastructure and service performance of the piped water supply system in Depok City, Indonesia, in relation to national and international benchmarks. Despite recent developments, the service coverage in 2024 only reached 22.33%, falling short of the RPJMN 2020–2024 target of 30%. Most residents (80.6%) still rely on groundwater due to affordability, accessibility, and trust issues. Projections indicate a substantial gap in water treatment capacity and reservoir storage, with an additional 1,250 L/s of treatment capacity and 40,000 m³ of storage required by 2045 to meet demand. The analysis also reveals a persistent Non-Revenue Water (NRW) rate of around 20%, indicating systemic inefficiencies. Institutional fragmentation and low community uptake of piped water services further hinder progress. Recommendations include infrastructure expansion, NRW reduction, stakeholder coordination, and community engagement. Furthermore, adopting smart water technologies and implementing a more integrated urban water management strategy are critical to achieving equitable access. The findings provide evidence-based insights for policymakers and utility providers to enhance water service delivery in rapidly urbanizing contexts while aligning with the Sustainable Development Goals and WHO standards.